2022
DOI: 10.1007/s11657-022-01073-1
|View full text |Cite
|
Sign up to set email alerts
|

An update of the prevalence of osteoporosis, fracture risk factors, and medication use among community-dwelling older adults: results from the Canadian Longitudinal Study on Aging (CLSA)

Abstract: Summary The prevalence of self-reported and DXA-confirmed osteoporosis was 7.8% (males 2.2%; females 12.7%), and 3.6% (males 1.2%; females 5.9%), respectively. We found that most community-dwelling older adults at high fracture risk are not taking osteoporosis medication, particularly males. There is a major opportunity for improved primary fracture prevention in the community. Purpose To provide an up-to-date prevalence es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This may be because females are more likely to take an osteoporosis medication, which could affect their BMD. Males are often undertreated for osteoporosis and are less likely to be taking medication [ 49 ]. Our study did not adjust for osteoporosis medication use because we could not access data on these medications.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because females are more likely to take an osteoporosis medication, which could affect their BMD. Males are often undertreated for osteoporosis and are less likely to be taking medication [ 49 ]. Our study did not adjust for osteoporosis medication use because we could not access data on these medications.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al conducted a systematic review and meta-analysis, which found that the global prevalence of osteoporosis was 19.7% according to the World Health Organization diagnostic criteria and the prevalence varied greatly in different countries (from 4.1% in Netherlands to 52.0% in Turkey) and continents (from Oceania 8.0% to 26.9% in Africa) [ 16 ]. The prevalence of physician diagnosed and DXA-confirmed osteoporosis was 12.7% and 5.9% in females, respectively based on data from community-dwelling older adults from the Canadian Longitudinal Study on Aging [ 17 ]. Buttros and cols conducted a cross-sectional study and found a prevalence of 24.6% of osteoporosis in postmenopausal women (aged 40–75 years) using BMD for diagnosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the treatment rate of osteoporosis patients was decreased during 2005–2018. Previously, McArthur et al observed that for community-dwelling older adults who have already diagnosed with osteoporosis, 76.8% females were not taking an osteoporosis medication [ 17 ]. A systematic review and meta-analysis identified that the treatment rate of osteoporosis in patients undergoing total knee and hip arthroplasty patients was 32.9% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%